Connectors for electrical and electronic equipment. Product requirements. Circular connectors. Detail specification for connectors with M8 screw-locking with power contacts and signal contacts for data transmission up to 100 MHz Part 2-114, (4th November 2020) - British Standards Institution,
No abstract available